Barriers and facilitators of a near real-time feedback approach for measuring patient experiences of hospital care. Issue 1 (March 2017) - Käsbauer, Susanne; Cooper, Robyn; Kelly, Laura; King, Jenny
Abstract: Objectives: To contribute towards the current policy directive and recommendations outlined in the Francis Report (1) to strengthen relational aspects of hospital care and increase the use of a near real-time feedback (RTF) approach. This article offers insight into the challenges and enablers faced when collecting near real-time feedback of patient experiences with trained volunteers; and using the data to facilitate improvements. Methods: Feedback was collected from staff and volunteers before, during and after a patient experience data collection. This took the form of both formal mixed methods data collections via interviews, surveys and a diary; and informal anecdotal evidence, collected from meetings, workshops, support calls and a networking event. Results: Various challenges and enablers associated with the RTF approach were identified. These related to technology, the setting, volunteer engagement and staff engagement. This article presents the key barriers experienced followed by methods suggested and utilised by staff and volunteers in order to counteract the difficulties faced. Conclusions: The results from this evaluation suggest that a near real-time feedback approach, when used in a hospital setting with trained volunteers, benefits from various support structures or systems to minimise the complications or burden placed on both staff and volunteers. Highlights: A near real-time feedback approach to collect patient experience data in hospitals using trained volunteers. Empirical and anecdotal evidence collected from hospitals to understand the success of the near real-time feedback approach. Feedback from volunteers and staff explores barriers and facilitators of the approach and subsequent use of the results. Various support systems and structures can mitigate challenges associated with a near real-time feedback approach.